EFEKTIFITAS BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING UNTUK MENGURANGI PERILAKU AGRESIF VERBAL SISWA KELAS VIII MTS AL-HIDAYAH BEKASI - Fadhil Hardiansyah; Siti Robiah Adawiyah (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2016)
Effectiveness Group Guidance With ModellingTechniques For Diminish Verbal Aggressive Behavior Students Of Grade VIII MTs AlHidayah Bekasi. Theme of mini thesis. Program Study Guidance and Counseling. FacultyTeaching Science Education Universitas Islam Asyafiiyah.This research is motivated by descend of morals adolescent on this period, especiallyverbal aggressive behavior. As we know it there are many incident happened to them whocan't be controlled by education. There are many happened act of despising verbals, tauntwith vile language, threaten, said in a lound tone, heckle and slovenly who can makecommotion, brawl, engage in a gang fight even killing. with this research be expected tocapable of providing provisioning to student can understand behaviour who can acceptedbysociety and can't to.The purpose of this research is to test for get data’s empirical and information theeffectiviness group guidance with modelling tecqniques for diminish verbal aggressivebehavior students of grade VIII MTs Al-Hidayah Bekasi.The research is quasi exerimental design with reaserch design non equivalent contolgroup design. Subject of this research are the students of eight grade at MTs Al-HidayahBekasi in acadenic year of 2015/2016 who have high verbal aggressive behavior. Thesubjects numbering 24 persons. This subject will be divided into two group of 12 persons intothe experimental group and 12 persons control group. The collection teqnigue of data useverbal aggressive behavior questionnaire. Validite data use product moment of ms. Exel andcalculation manual.The result of the analysis showed = 2,834, ttabel=2,072 with significance (α =0,05) dk = n1+n2-2=12+12–2=22. For result research seen that ttest≥ ttable. Hipotesis nihil (Ho)to exlain “Group guidance with modelling tecqniques not effective for diminish verbalaggressive behavior students of grade VIII MTs Al-Hidayah Bekasi” rejecting. Whilehipotesis alternatif (Ha) to explain “Group guidance with modelling tecqniques effective fordiminish verbal aggressive behavior students of grade VIII MTs Al-Hidayah Bekasi”accepting.Conclusions this research group guidance with modelling tecqniques effective todiminish verbal aggressive behavior students of grade VIII MTs Al-Hidayah Bekasi.